Research on the Balance Efficiency of the Intelligent Hanging System for Jeans Production Line - Huo, Yarui; Faridah, Sahari (Atlantis Press, 2023)
Intelligent manufacturing is an important strategic direction for transforming and upgrading China’s manufacturing industry, and the study of balance efficiency is the core of intelligent production. The introduction of intelligent hanging in the jeans production line is imperative to help balance the production line. Based on the information system success model, this paper explores the impact factors of introducing the intelligent hanging system on the balance efficiency of the jeans production line. According to the 2696 valid questionnaires obtained and the structural equation modeling, research has found that (i) information quality has a significant positive impact on user satisfaction and usage intention; (ii) user satisfaction positively affects usage intention. (iii) Both user satisfaction and intention to use positively impact balance efficiency. Finally, combined with the results of data analysis, practical suggestions were made for introducing intelligent equipment in jeans production lines to promote production line balancing.